2018
DOI: 10.1021/acs.joc.8b02190
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nitriles from Primary Amides or Aldoximes under Conditions of a Catalytic Swern Oxidation

Abstract: The preparation of nitriles from primary amides or aldoximes was achieved by using oxalyl chloride with a catalytic amount of dimethyl sulfoxide in the presence of Et3N. The reactions were complete within 1 h after addition at room temperature. A diverse range of cyano compounds were obtained in good to excellent yields, including aromatic, heteroaromatic, cyclic, and acyclic aliphatic species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 38 publications
(43 reference statements)
0
39
0
Order By: Relevance
“…In addition, researchers have found that primary amides or aldoximes can be dehydrated to give nitriles 103 under Swern oxidation conditions (Scheme ) …”
Section: Dehydrationmentioning
confidence: 99%
“…In addition, researchers have found that primary amides or aldoximes can be dehydrated to give nitriles 103 under Swern oxidation conditions (Scheme ) …”
Section: Dehydrationmentioning
confidence: 99%
“…To date, various methods for the synthesis of nitriles have been developed using different starting substrates, reagents and reaction conditions (Scheme ). Nitriles have been prepared from amines ( I ), amides ( II ), aldehydes ( III ), oximes ( IV ), amidoximes ( V ), thioamides ( VI ), alkyl‐halides/azides ( VII ), nitroalkanes ( VIII ), anilines/arylhalides ( IX ), and alcohols ( X ) . On larger scale, nitriles are commonly produced via the ammoxidation or hydrocyanation methods .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Oximes serve as key synthons for the preparation of carbonyl amines, nitriles, amides, thiohydroxamic and thiohydroxic acid derivatives, nitro compounds, and oxime esters. [7][8][9][10][11][12][13][14] For example, cyclohexanone oxime is widely used in industry as a key intermediate for the synthesis of caprolactam, which is the precursor of Nylon 6. 15 Oximes have also drawn considerable attention in supramolecular chemistry due to their ability to both accept and donate hydrogen bonds and thus their capacity to form dimers and catemers.…”
Section: Introductionmentioning
confidence: 99%